Internship Learning Experience of Business Students of Pokhara University in Kathmandu Valley (Quest Journal of Management and Social Sciences, 2026)
Background: Internships bridge the gap between theoretical learning and practical workplace experience, providing students with opportunities to apply academic knowledge in real-world settings. Globally, internships are recognized as essential for developing professional skills, enhancing employability, and shaping career trajectories. In Nepal, Pokhara University emphasizes internships as part of business education, yet there is limited empirical evidence on how these experiences influence students’ career development, satisfaction, and promotion of internship programs through word-of-mouth, particularly in the Kathmandu Valley.Purpose: Internships provide students with opportunities to gain practical work experience and enhance learning through structured, supervised engagement. This study examines the experiences and impact of internships on the career development of business students at Pokhara University in the Kathmandu Valley.Design/Methodology/Approach: An explanatory research design was employed, guided by the Expectation Confirmation Theory. A probability sampling technique was used to survey 391 management students. Data collection was conducted using KOBO Toolbox, while data analysis was performed with PLS-SEM, and Microsoft Excel was utilized for data entry and tabulation.Findings: The study finds that students perceive internships as an essential component of their education, providing valuable work experience. However, challenges exist, including organizational issues, time management, role assignment, and treatment of interns. Internship experiences significantly influence students’ future career intentions and their likelihood of recommending the program (word of mouth). Managerial strategies to enhance internship effectiveness are also discussed.Conclusion: Internships play a critical role in shaping business students’ career trajectories and influencing word-of-mouth promotion of internship programs. Satisfaction with internship experiences mediates both future career intentions and word-of-mouth behavior. Addressing the challenges faced by students during internships is essential to maximize their educational and professional benefits.Keywords: Internship, Business Students, Internship Experience, Career Development, Word of Mouth